LEGAL PROTECTION FOR INDONESIAN CITIZENS IN LAND OWNERSHIP DISPUTES INCLUDED IN COAL MINING BUSINESS PERMIT CONCESSIONS - Leonard Ibsan Kapasian; Oni Rosifany; Khairunnisah; Irman Syahriar (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
This study examines the form and effectiveness of legal protection for Indonesian citizens in guaranteeing land ownership within coal mining concession areas. The primary focus is on the tension between national economic interests in the mining sector and community land rights guaranteed by the constitution. This study uses a normative juridical method with a regulatory approach, legal theory, and empirical case studies in several mining areas such as Kutai Kartanegara and Paser. The results indicate that land conflicts in IUP areas are generally revoked due to overlapping ownership claims, weak land administration verification (SKT/SKPT), and minimal government oversight. The state, based on the theory of the Right to Control (HMN), has a constitutional mandate to regulate, manage, and oversee the utilization of natural resources for the welfare of the people. However, its implementation is still biased towards corporate interests, so that community rights are often neglected. This study recommends the implementation of responsive laws, strengthening the social function of land rights, and transparent and pro-community mechanisms for peace and conservation resolution. True legal protection can only be achieved if the state acts not merely as a regulator but also as an active protector of citizens' rights against the impacts of the expansion of the coal mining industry.